The GeoPT Proficiency Testing Programme as a Scheme for the Certification of Geological Reference Materials. Issue 3 (29th March 2019) - Potts, Philip J.; Webb, Peter C.; Thompson, Michael
Abstract : ISO Guide 35:2017 provides, for the first time, an alternative way of characterising certified reference materials using proficiency testing. In this paper, the properties of assigned values derived from the well‐established Geo PT proficiency testing scheme are examined. This scheme, designed for laboratories that undertake the routine analysis of silicate rocks and related materials, routinely has over 100 participants contributing results. Following a detailed assessment of the metrological properties of Geo PT assigned values in relation to Guide 35 recommendations, it is demonstrated that these values may be regarded as certified values, provided a number of criteria are met. These criteria include the following: a demonstration of sufficient homogeneity of the candidate CRM; circulation, when judged to be appropriate, of an established matrix‐matched CRM for co‐analysis in that round; the robust statistical analysis of data sets using Geo PT established criteria; a decision whether assigning a value is justified (including a requirement of a minimum of fifteen valid results); and an expert group to manage the certification and the maintenance of appropriate records. In summary, the Geo PT proficiency testing scheme, subject to the arrangements summarised above, is considered to be competent for the certification of geological reference materials. Key Points: Geo PT is a mature proficiency testing scheme in which assigned values have proved to be effective estimates of true values. Assigned values and corresponding uncertainties are assessed from measurement results contributed by large numbers of laboratories. Subject to specified conditions the Geo PT scheme is considered suitable for certification of geological reference materials.